Wind loads for petrochemical and other industrial facilities (American Society of Civil Engineers, 2011)
Prepared by the Task Committee on Wind-Induced Forces of the Petrochemical Committee of the Energy Division of ASCE. Wind Loads for Petrochemical and Other Industrial Structures provides state-of-the-practice guidelines for the computation of wind-induced forces on industrial facilities with structural features outside the scope of current codes and standards. Without adequate standards, companies and their engineers developed techniques to calculate the wind loads for their facilities. The result is a wide variation in practice and inconsistent structural reliability. To encourage uniform wind load calculations, this report first reviews existing design practices for pipe racks and bridges, open and partially clad frame structures, vessels, tanks, steel stacks, cooling towers, and air coolers. Then, recommended guidelines are presented for design methods and the analytical determination of wind loads. Worked calculations for six example situations are included to illustrate the application of the recommended guidelines. This report is intended for use by engineers who design industrial facilities and assumes familiarity with Standard ASCE 7, Minimum Design Loads for Buildings and Other Structures. It will also be useful to company managers who are responsible for establishing wind-load design and construction standards and to local building authorities.
Keywords: Petroleum refineries -- Design and construction.; Industrial buildings -- Design and construction.; Petroleum refineries -- Aerodynamics.; Industrial buildings -- Aerodynamics.; Wind-pressure.; elektronické knihy; electronic books